Doebner-type pyrazolopyridine carboxylic acids in an Ugi four-component reaction - Murlykina, Maryna V.; Kolomiets, Oleksandr V.; Kornet, Maryna M.; Sakhno, Yana I.; Desenko, Sergey M.; Dyakonenko, Victoriya V.; Shishkina, Svetlana V.; Brazhko, Oleksandr A.; Musatov, Vladimir I.; Tsygankov, Alexander V.; Van der Eycken, Erik V.; Chebanov, Valentyn A. (Beilstein Journal of Organic Chemistry, 2019)
Substituted 1H-pyrazolo[3,4-b]pyridine-4- and 1H-pyrazolo[3,4-b]pyridine-6-carboxamides have been synthetized through a Doebner–Ugi multicomponent reaction sequence in a convergent and versatile manner using diversity generation strategies: combination of two multicomponent reactions and conditions-based divergence strategy. The target products contain as pharmacophores pyrazolopyridine and peptidomimetic moieties with four points of diversity introduced from readily available starting materials including scaffold diversity. A small focused compound library of 23 Ugi products was created and screened for antibacterial activity.
Keywords: antibacterial activity; Doebner reaction; pyrazolo[3,4-b]pyridine carboxylic acids; Ugi reaction

(untitled) - Ruijter, E.; Scheffelaar, R.; Orru, R. V. A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Dömling, A.; Ugi, I. (Angew. Chem., Int. Ed. Engl., 1993)

(untitled) - Elders, N.; van der Born, D.; Hendrickx, L. J. D.; Timmer, B. J. J.; Krause, A.; Janssen, E.; de Kanter, F. J. J.; Ruijter, E.; Orru, R. V. A. (Angew. Chem., Int. Ed., 2009)

(untitled) - Welsch, M. E.; Snyder, S. A.; Stockwell, B. R. (Curr. Opin. Chem. Biol., 2010)

(untitled) - Marcaurelle, L. A.; Foley, M. A. (Curr. Opin. Chem. Biol., 2010)

(untitled) - Cowen, S. D.; Russell, D.; Dakin, L. A.; Chen, H.; Larsen, N. A.; Godin, R.; Throner, S.; Zheng, X.; Molina, A.; Wu, J.; Cheung, T.; Howard, T.; et al. (J. Med. Chem., 2016)

(untitled) - Giannouli, V.; Lougiakis, N.; Kostakis, I. K.; Pouli, N.; Marakos, P.; Skaltsounis, A.-L.; Nam, S.; Jove, R.; Horne, D.; Tenta, R.; Pratsinis, H.; Kletsas, D. (Bioorg. Med. Chem. Lett., 2016)

(untitled) - Wenglowsky, S. (Expert Opin. Ther. Pat., 2013)

(untitled) - Ahmed, O. M.; Mohamed, M. A.; Ahmed, R. R.; Ahmed, S. A. (Eur. J. Med. Chem., 2009)

(untitled) - Abdel-Mohsen, S. A.; El-Emary, T. I. (Pharma Chem., 2018)

(untitled) - Foks, H.; Pancechowska-Ksepko, D.; Kędzia, A.; Zwolska, Z.; Janowiec, M.; Augustynowicz-Kopeć, E. (Farmaco, 2005)

(untitled) - Patel, J. B.; Malick, J. B.; Salama, A. I.; Goldberg, M. E. (Pharmacol., Biochem. Behav., 1985)

(untitled) - Dodiya, D. K.; Trivedi, A. R.; Kataria, V. P.; Shah, V. H. (Curr. Org. Chem., 2012)

(untitled) - Soural, M.; Bouillon, I.; Krchnák, V. (J. Comb. Chem., 2008)

(untitled) - Edraki, N.; Firuzi, O.; Fatahi, Y.; Mahdavi, M.; Asadi, M.; Emami, S.; Divsalar, K.; Miri, R.; Iraji, A.; Khoshneviszadeh, M.; Firoozpour, L.; Shafiee, A.; et al. (Arch. Pharm. (Weinheim, Ger.), 2015)

(untitled) - He, L.-J.; Yang, D.-L.; Li, S.-Q.; Zhang, Y.-J.; Tang, Y.; Lei, J.; Frett, B.; Lin, H.-k.; Li, H.-y.; Chen, Z.-Z.; Xu, Z.-G. (Bioorg. Med. Chem., 2018)

(untitled) - Avilés, E.; Prudhomme, J.; Le Roch, K. G.; Franzblau, S. G.; Chandrasena, K.; Mayer, A. M. S.; Rodríguez, A. D. (Bioorg. Med. Chem. Lett., 2015)

(untitled) - Huang, Y.; Wolf, S.; Bista, M.; Meireles, L.; Camacho, C.; Holak, T. A.; Dömling, A. (Chem. Biol. Drug Des., 2010)

(untitled) - Ingold, M.; Dapueto, R.; Victoria, S.; Galliusi, G.; Batthyàny, C.; Bollati-Fogolín, M.; Tejedor, D.; García-Tellado, F.; Padrón, J. M.; Porcal, W.; López, G. V. (Eur. J. Med. Chem., 2018)

(untitled) - Yang, S.; Jyothi, K. R.; Lim, S.; Choi, T. G.; Kim, J.-H.; Akter, S.; Jang, M.; Ahn, H.-J.; Kim, H.-Y.; Windisch, M. P.; Khadka, D. B.; Zhao, C.; et al. (J. Med. Chem., 2015)

(untitled) - Azuaje, J.; El Maatougui, A.; García-Mera, X.; Sotelo, E. (ACS Comb. Sci., 2014)

(untitled) - Che, C.; Li, S.; Yu, Z.; Li, F.; Xin, S.; Zhou, L.; Lin, S.; Yang, Z. (ACS Comb. Sci., 2013)

(untitled) - Ghandi, M.; Zarezadeh, N.; Abbasi, A. (Org. Biomol. Chem., 2015)

(untitled) - Shaw, A. Y.; Xu, Z.; Hulme, C. (Tetrahedron Lett., 2012)

(untitled) - Xu, Z.; Martinez-Ariza, G.; Cappelli, A. P.; Roberts, S. A.; Hulme, C. (J. Org. Chem., 2015)

(untitled) - Balalaie, S.; Saeedi, S.; Ramezanpour, S. (Helv. Chim. Acta, 2016)

(untitled) - Konstantinidou, M.; Kurpiewska, K.; Kalinowska-Tłuscik, J.; Dömling, A. (Eur. J. Org. Chem., 2018)

(untitled) - Liao, W.-L.; Li, S.-Q.; Wang, J.; Zhang, Z.-Y.; Yang, Z.-W.; Xu, D.; Xu, C.; Lan, H.-T.; Chen, Z.-Z.; Xu, Z.-G. (ACS Comb. Sci., 2016)

(untitled) - Caputo, S.; Basso, A.; Moni, L.; Riva, R.; Rocca, V.; Banfi, L. (Beilstein J. Org. Chem., 2016)

(untitled) - Zheng, Q.; Mi, N.; Fan, Z.; Zuo, X.; Zhang, H.; Wang, H.; Yang, Z. (J. Agric. Food Chem., 2010)

(untitled) - Sheikhhosseini, E.; Balalaie, S.; Bigdeli, M. A.; Habibi, A.; Moghaddam, H. P. (J. Korean Chem. Soc., 2014)

(untitled) - Kumar, S.; Mukesh, K.; Harjai, K.; Singh, V. (Tetrahedron Lett., 2019)

(untitled) - Alavijeh, N. S.; Ramezanpour, S.; Alavijeh, M. S.; Balalaie, S.; Rominger, F.; Misra, A.; Bijanzadeh, H. R. (Monatsh. Chem., 2014)

(untitled) - Plant, A.; Thompson, P.; Williams, D. M. (J. Org. Chem., 2009)

(untitled) - Beaumont, S.; Retailleau, P.; Dauban, P.; Dodd, R. H. (Eur. J. Org. Chem., 2008)

(untitled) - Van den Bogaert, A. M.; Nelissen, J.; Ovaere, M.; Van Meervelt, L.; Compernolle, F.; De Borggraeve, W. M. (Eur. J. Org. Chem., 2010)

(untitled) - Mahdavi, M.; Hassanzadeh-Soureshjan, R.; Saeedi, M.; Ariafard, A.; BabaAhmadi, R.; Ranjbar, P. R.; Shafiee, A. (RSC Adv., 2015)

(untitled) - Purohit, P.; Pandey, A. K.; Kumar, B.; Chauhan, P. M. S. (RSC Adv., 2016)

(untitled) - Madhavachary, R.; Naveen, N.; Wang, Y.; Wang, Q.; Konstantinidou, M.; Dömling, A. (Eur. J. Org. Chem., 2018)

(untitled) - Pandey, S.; Khan, S.; Singh, A.; Gauniyal, H. M.; Kumar, B.; Chauhan, P. M. S. (J. Org. Chem., 2012)

(untitled) - Balalaie, S.; Bararjanian, M.; Hosseinzadeh, S.; Rominger, F.; Bijanzadeh, H. R.; Wolf, E. (Tetrahedron, 2011)

(untitled) - Rasouli, M. A.; Mahdavi, M.; Firoozpour, L.; Shafiee, A.; Foroumadi, A. (Tetrahedron, 2014)

(untitled) - Al-Tel, T. H.; Al-Qawasmeh, R. A.; Voelter, W. (Eur. J. Org. Chem., 2010)

(untitled) - Castellano, T. G.; Neo, A. G.; Marcaccini, S.; Marcos, C. F. (Org. Lett., 2012)

(untitled) - Chebanov, V. A.; Sakhno, Y. I.; Desenko, S. M.; Chernenko, V. N.; Musatov, V. I.; Shishkina, S. V.; Shishkin, O. V.; Kappe, C. O. (Tetrahedron, 2007)

(untitled) - Murlykina, M. V.; Sakhno, Y. I.; Desenko, S. M.; Konovalova, I. S.; Shishkin, O. V.; Sysoiev, D. A.; Kornet, M. N.; Chebanov, V. A. (Tetrahedron, 2013)

(untitled) - Sakhno, Y. I.; Murlykina, M. V.; Morozova, A. D.; Kozyryev, A. V.; Chebanov, V. A. (Fr.-Ukr. J. Chem., 2015)

(untitled) - Murlykina, M. V.; Morozova, A. D.; Zviagin, I. M.; Sakhno, Y. I.; Desenko, S. M.; Chebanov, V. A. (Front. Chem. (Lausanne, Switz.), 2018)

(untitled) - Sakhno, Y. I.; Kozyryev, A. V.; Desenko, S. M.; Shishkina, S. V.; Musatov, V. I.; Sysoiev, D. O.; Chebanov, V. A. (Tetrahedron, 2018)

(untitled) - Sakhno, Y. I.; Desenko, S. M.; Shishkina, S. V.; Shishkin, O. V.; Sysoyev, D. O.; Groth, U.; Kappe, C. O.; Chebanov, V. A. (Tetrahedron, 2008)

(untitled) - Murlykina, M. V.; Sakhno, Y. I.; Desenko, S. M.; Shishkina, S. V.; Shishkin, O. V.; Sysoiev, D. O.; Kornet, M. N.; Schols, D.; Goeman, J. L.; Van der Eycken, J.; Van der Eycken, E. V.; Chebanov, V. A. (Eur. J. Org. Chem., 2015)

(untitled) - Annan, N.; Paris, R.; Jordan, F. (J. Am. Chem. Soc., 1989)

(untitled) - Meng, Q.; Zhu, L.; Zhang, Z. (J. Org. Chem., 2008)

Selective Toxicity: the physico-chemical basis of therapy - Albert, A. (Springer, 1985)